2018
DOI: 10.4148/1944-9771.1159
|View full text |Cite
|
Sign up to set email alerts
|

Financial Infidelity in Couple Relationships

Abstract: Four hundred and fourteen participants answered questions regarding financial habits within the context of the couple relationship. The Big Five Personality Inventory and a Martial and Life Satisfaction Scale were used to determine the incidence and factors associated with financial infidelity. Results indicated that 27% of participants have kept a financial secret from their partner. Furthermore, both marital and life satisfaction were lower for participants who have experienced financial infidelity than in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…Specific issues we control for that may act as proxies for structural commitment include the age and marital duration of an individual (e.g., the longer the previous marriage, the more difficult it will be to split finances and, perhaps, find a new romantic partner), one's education level (e.g., lower levels of education may make a spouse more financially dependent on the other), and race/ethnicity (e.g., the acceptability of divorce may vary across race/ethnic groups). Neither of the previous quantitative studies that have examined the predictors of financial deception (Jeanfreau et al, 2018;Junare & Patel, 2012) have found gender differences in marital financial deception. However, given the historic gendered financial power within marriage (Zelizer, 1997) and the fact that issues of relationship power can still be associated with financial issues in marriage (LeBaron et al, 2019), we controlled for sex.…”
Section: Structural Commitmentmentioning
confidence: 93%
See 2 more Smart Citations
“…Specific issues we control for that may act as proxies for structural commitment include the age and marital duration of an individual (e.g., the longer the previous marriage, the more difficult it will be to split finances and, perhaps, find a new romantic partner), one's education level (e.g., lower levels of education may make a spouse more financially dependent on the other), and race/ethnicity (e.g., the acceptability of divorce may vary across race/ethnic groups). Neither of the previous quantitative studies that have examined the predictors of financial deception (Jeanfreau et al, 2018;Junare & Patel, 2012) have found gender differences in marital financial deception. However, given the historic gendered financial power within marriage (Zelizer, 1997) and the fact that issues of relationship power can still be associated with financial issues in marriage (LeBaron et al, 2019), we controlled for sex.…”
Section: Structural Commitmentmentioning
confidence: 93%
“…Having negative feelings toward a spouse or receiving negative feelings from a spouse may weaken the bonds of moral commitment and lead one to engage in infidelity or deception—whether emotional, sexual, or financial. Thus, individuals who deceive their spouse in one domain (e.g., the sexual domain) are likely to deceive their spouse in other domains (e.g., the financial domain; Jeanfreau et al, 2018) due to underlying feelings toward their spouse (Allen et al, 2005; Johnson, 2008; Whisman et al, 2007). Hypothesis Individuals who deceive in emotional/sexual fidelity will be more likely to be in a higher financial deception group.…”
Section: Marital Financial Deception and Its Predictorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fraud/ financial deceit: Fraud is the type of deception that includes financial ramification. Examples may include lyingabout money spent, misusing partner's money (Jeanfreau, et. al., 2018).…”
Section: Suggestions and Recommendations For Future Studiesmentioning
confidence: 99%
“…Spousal identity theft is a form of familiar identity theft as well as a form of financial infidelity and occurs when an individual uses the personal identifying information of his/her spouse without consent for personal gain. According to Jeanfreau, Noguchi, Mong, and Stadthagen (2018), "Financial infidelity may be defined as a form of financial cheating that one partner commits with his or her current partner" (p. 2).…”
Section: Perpetrators Of Familiar Identity Theftmentioning
confidence: 99%